The Epidemiology of Invasive Group B Streptococcus in Denmark From 2005 to 2018 - Slotved, Hans-Christian; Hoffmann, Steen (Frontiers in Public Health, 2020)
Previous epidemiology reports on invasive Streptococcus agalactiae (GBS) infections in Denmark did not include all patient age groups. The aim of this study was therefore to analyse the GBS incidence in all age groups during the period 2005 – 2018 and present the serotype distribution and the antibiotic susceptibility. Data were retrieved from the Danish laboratory surveillance system, and included data on typing and susceptibility testing for erythromycin and clindamycin. Early-onset disease (EOD) (mean incidence 0.17 per 1,000 live births) and late-onset disease (LOD) (mean incidence 0.14 per 1,000 live births) showed a low level during the period. The incidence was stable in the age groups 91d (days) to 4y (years), 5y-19y, and 20y-64y. The elderly showed a significantly increasing trend (P < 0.05) in the incidence from 2005 to 2018, 65y-74y increased from 3.23 to 8.34 per 100,000, while 75y+ increased from 6.85 to 16.01 per 100,000. Erythromycin and clindamycin resistance fluctuated over the period, however, the overall trend was increasing. Data showed that EOD and LOD incidence continued to be low, while an increasing trend in GBS infections in the elderly was observed. The prevalence of erythromycin and clindamycin resistance increased from 2005 - 2018.